The Analysis of Climatic Characteristics Influencing Amala Tourist Project Area - Ben Hasher , Fahdah (Dirasat: Human and Social Sciences, 2022)
This research provides an analysis of the climate elements affecting the Amala Tourism Project area, which is located between the governorates of Umluj in the south and Al Wajh in the north in the Tabuk region, northwest of the Kingdom of Saudi Arabia. - Study objectives: Depending on the importance of the subject of study, it seeks to achieve the following objectives: 1- Analyzing the statistical characteristics of five climatic elements in Al Wajh stations (40400) located within the area of the project and Tabuk (40375) located in the north 2- Analyzing temporal variations of temperature, relative humidity and wind speed affecting the area of the Amala tourism project. 3- Determine the climatic characteristics affecting the tourism activity in the Amala project area, using the limits of temperature, relative humidity and wind speed appropriate for human activity and comfort. 4- Estimation of the daily evapotranspiration by applying Al Jarash model and the daily solar radiation by applying the Hargreaves-Samani model.This study reached to determine the statistical characteristics of the climatic elements data (temperature, relative humidity, wind speed) affecting human comfort and his daily activity in the Amla Tourism Project area. This study was also able to determine the characteristics of the temporal variations of these elements using the monthly relative frequency distribution in Al-Wajh and Tabuk stations. The monthly relative frequency method helped to identify the best periods of human comfort and his daily activity in the Amala Tourism Project area.